Assessing the Long-Term Prospects of Peace: A Normative Analysis of the Helsinki Memorandum of Understanding in Ensuring Human Rights and Reconciliation in Aceh: Mengukur Nafas Panjang Perdamaian: Analisis Normatif MoU Helsinki dalam Menjamin Hak Asasi dan Rekonsiliasi di Aceh - Prayogo, Andri Rafi; Heriyanto, Dodik Setiawan Nur (Lex Renaissance, 2025)
This research investigates two questions: (i) how far the MoU and its implementing legislation have remedied pre-existing human-rights violations arising from the internal armed conflict; and (ii) whether the present institutional framework fulfils the MoU’s promise of sustainable post-conflict justice. Anchored in a normative juridical methodology, the study deploys statute and conceptual approaches to examine primary legal sources—inter alia the 1945 Constitution, Law No. 11/2006 on Aceh Governance, Law No. 26/2000 on Human Rights Courts—and authoritative jurisprudence, scholarly commentary and human-rights reports. Findings indicate that the MoU was pivotal in terminating hostilities, demobilising combatants and recognising Aceh’s special autonomy; however, it falls short of constituting a comprehensive justice mechanism. Persistent obstacles include the absence of a Human Rights Court seated in Banda Aceh, the circumscribed mandate and chronic under-funding of the Aceh Truth and Reconciliation Commission, low prosecution rates for grave abuses such as enforced disappearances, inadequate reparations for victims and uneven reintegration support for ex-combatants, women and child survivors. Consequently, the Aceh transitional-justice architecture remains fragmented, reactive and overly dependent on Jakarta’s political will. The article contends that realising the MoU’s transformative potential requires harmonising national legislation with international human-rights standards, building local institutional capacity and embedding victim-centred restorative programmes within Aceh’s broader development agenda. Strengthening these normative and institutional pillars is essential to truly convert the MoU from a mere cessation-of-violence agreement into a durable framework for restorative justice and reconciliation.